Mosquito transgenesis: what is the fitness cost? - Marrelli, Mauro T.; Moreira, Cristina K.; Kelly, David; Alphey, Luke; Jacobs-Lorena, Marcelo (Trends in parasitology, 2006)
The generation of transgenic mosquitoes with a minimal fitness load is a prerequisite for the success of strategies for controlling mosquito-borne diseases using transgenic insects. It is important to assemble as much information as possible on this subject because realistic estimates of transgene fitness costs are essential for modeling and planning release strategies. Transgenic mosquitoes must have minimal fitness costs, because such costs would reduce the effectiveness of the genetic drive mechanisms that are used to introduce the transgenes into field mosquito populations. Several factors affect fitness of transgenic mosquitoes, including the potential negative effect of transgene products and insertional mutagenesis. Studies to assess fitness of transgenic mosquitoes in the field (as opposed to the laboratory) are still needed.